Definition of persistent areas with increased dengue risk by detecting clusters in populations with differing mobility and immunity in Rio de Janeiro, Brazil - Jefferson Pereira Caldas dos Santos; Nildimar Alves Honório; Aline Araújo Nobre (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Dengue is a re-emerging arbovirus infection of major epidemiological importance. The detection of dengue clusters is an important epidemiological surveillance strategy, contributing to better allocation of control measures and prioritizing areas that are subject to increased risk of transmission. Studies involving human populations with low mobility are scarce, and the current study thus aims to investigate the presence of persistent dengue clusters in the city of Rio de Janeiro, Brazil, in populations with different mobility and immunity. Epidemiological data on dengue were obtained from the Brazilian Ministry of Health. Areas of increased risk were defined by the space-time scan statistical method and analysis of persistence with use of map algebra. For both study populations, the clusters that were identified did not show spatial concordance, except in years when both presented the same immunological profile. Their persistent clusters were located mostly in the West Zone of city. The clusters of the two study populations only displayed spatial concordance in years with similar immune profiles, which confirms the confounding role of immunity and supports the use of populations with high percentages of susceptible individuals when designing territory-based dengue studies. The space-time similarity between the areas of persistent risk in both populations suggests that the West Zone, a region with disorderly urban growth and low mean income, shows the highest risk of dengue transmission. The definition of persistent dengue clusters contributes to the improvement of dengue control strategies and territorial planning.